A study on the codon usage bias of arenavirus common genes - Thomas, Pablo Daniel; Ferrer, María Florencia; Lozano, Mauricio J.; Gómez, Ricardo Martín (Frontiers in Microbiology, 2025)
IntroductionThe Arenaviridae family consists of the genera Mammarenavirus, Reptarenavirus, Hartmanivirus, Antennavirus and Innmovirus. The codon usage bias between the different genera has not yet been studied comparatively.MethodsWe retrieved the arenavirus genome sequences from public databases and used bioinformatics tools to compare the codon usage bias between the different genera for the GPC, NP and L proteins, common to all arenaviruses.Results and discussionHartmaniviruses show a larger codon usage bias, which can be partially explained by mutational bias. Patterns of relative use of synonymous codons were maintained within genera, with individual genera differing in their preference for the third nucleotide position in synonymous codons. Of the three proteins examined, the ARN polymerase L protein exhibited a slightly stronger codon usage bias, but overall, the patterns were repeated between genera for the three proteins examined. Our results suggest that codon usage pattern bias in arenaviruses is influenced by selection pressure and to a lesser extent by mutational selection.